(untitled) (Proceedings of International Educators Conference, 2023)
In this article, the biggest war of Nadir Shah Afshar, the founder and most powerful king of the Afshar state in Iran, against the Babur Empire in 1739 and the details of the battle in Karnal and the defeat of the powerful army of the Babur ruler Mohammad Shah by Nadir Shah are given.